(untitled) - Tiffen, Rodney (Cambridge, 2004)
Australians find it difficult to compare themselves with the world because they exist as a developed English-speaking nation so far from the metropolitan centers of Europe and the U.S. Assessing the nation in relation to its broader group of peers, this book compares and contrasts Australia over 17 core aspects of economic, political and social life with 18 leading first-world countries. Rod Tiffen and Ross Gittins interpret the data and communicate its implications in this comprehensive reference work
Keywords: Australia,Australia,Australia,Úc,Úc,Úc; Politics and government,Economic conditions,Social life and customs,Chính trị và chính phủ,Điều kiện kinh tế,Đời sống xã hội và phong tục tập quán; 21st century,21st century,21st century,Thế kỷ 21,Thế kỷ 21,Thế kỷ 21